Patients with chronic periodontitis present increased risk for osteoporosis: A population‐based cohort study in Taiwan. (2nd May 2017) - Mau, L.‐P.; Kuan, Y.‐C.; Tsai, Y.‐W. C.; Lin, J.‐J.; Huynh‐Ba, G.; Weng, P.‐W.; Shieh, Y.‐S.; Cheng, W.‐C.; Huang, R.‐Y.
Abstract : Objectives: Chronic periodontitis is a bone destructive inflammatory disease with an adverse impact on general health and suggested underlying factors in common with osteoporosis. A few studies have examined the possible relationship between chronic periodontitis and osteoporosis; however, the results remain inconclusive. This longitudinal follow‐up study investigated the possible risk of patients with chronic periodontitis to present osteoporosis by using a population‐based national health insurance data set in Taiwan. Material and Methods: A random sample consisting of 1 million individuals was collected from Taiwan's national health insurance data set. From the sample, a total of 29 463 patients with newly diagnosed periodontitis from 2002 to 2008 were recruited and compared with a matched cohort of 58 926 patients without periodontitis. All patients were tracked until an osteoporosis diagnosis, or death, until the end of 2011. Associated factors, such as gender, age and comorbidities were examined. Cox proportional‐hazards regression was performed to examine the risk of osteoporosis for patients with or without periodontitis. Results: Within the 6‐year follow‐up period, the incidence rates of osteoporosis in the periodontitis cohort and comparison group were 2.72 and 1.66 per 1000 person‐years, respectively. Mild, moderate and severe periodontitis were found to have 1.56, 2.09 and 2.08 times the risk of osteoporosis respectively compared to patients without periodontitis. Log‐rank analysis revealed that patients with periodontitis had significantly higher cumulative incidence rates of osteoporosis than the control group ( P <.0001). Conclusion: This study found that patients with periodontitis had a higher risk of being diagnosed with osteoporosis.